PERAN KUALITAS PELAPORAN KEUANGAN DAN BUDAYA ORGANISASI DALAM MEMITIGASI PERSEPSI KORUPSI - Alfiana Antoh; Agustinus Salle (Universitas Cenderawasih, 2019)
Our study contributes by providing a new insight into the relationship between the quality of financial reporting with perceptions of corruption and how the relationship is moderated by organizational culture. In this article we argue that good quality of financial reporting will reduce perceptions of corruption and a strong organizational culture will further reduce perceptions of corruption. Data was collected by distributing questionnaires to 100 students of the Cenderawasih University Post-graduate program who were local government employees and were processed using moderated regression analysis (MRA). The result support the argument that organizational culture negatively influences perceptions of corruption while the effect of financial reporting quality and the influence of organizational culture moderation on perceptions of corruption are not supported. Finding related to the influence of organizational culture indicate that when there are values, norms and beliefs that are both applied within an organization, members of the organization will behave in accordance with these guidelines and will ultimately reduce the possibility of fraud.Keywords: Quality of Financial Reporting, Organizational Culture, Perception of Corruption, Local Government